1998
DOI: 10.1046/j.1523-1755.1998.00721.x
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic effects of dihydrotestosterone in immortalized mouse proximal tubule cells Technical Note

Abstract: Dihydrotestosterone (DHT) binding studies and the effects of DHT on the expression of beta-glucuronidase (Gus) and kidney androgen-regulated protein (KAP) genes and cell growth were investigated in immortalized early PKSV-PCT and late PKSV-PR proximal tubule cells, derived from transgenic mice carrying the L-pyruvate kinase/SV40 hybrid gene. [3H]DHT binding studies indicated that both cell lines have conserved substantial amounts of androgen receptors. The levels of KAP and Gus transcripts in PKSV-PCT cells, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…A decrease in 3␤-HSD4 expression could lead to an increase in dihydrotestosterone levels. Dihydrotestosterone has been demonstrated to cause an increase in cell proliferation in a proximal tubule cell line (25); thus decreased 3␤-HSD4 expression could result in increased proliferation of proximal tubule cells. Our results are consistent with this hypothesis as we found both a decrease in 3␤-HSD4 mRNA abundance and an increase in cell proliferation in kidneys from post-ovarian failure diabetic mice compared with cycling diabetic mice and control mice.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in 3␤-HSD4 expression could lead to an increase in dihydrotestosterone levels. Dihydrotestosterone has been demonstrated to cause an increase in cell proliferation in a proximal tubule cell line (25); thus decreased 3␤-HSD4 expression could result in increased proliferation of proximal tubule cells. Our results are consistent with this hypothesis as we found both a decrease in 3␤-HSD4 mRNA abundance and an increase in cell proliferation in kidneys from post-ovarian failure diabetic mice compared with cycling diabetic mice and control mice.…”
Section: Discussionmentioning
confidence: 99%
“…Relative CAT\β-gal activity shows that maximal efficiency occurs at the 1 µM DHT dose for both constructs in both cultured cell types. This concentration of DHT was previously reported to be the most effective in the induction of domes formed by PKSV-PCT and PKSV-PR cells, corresponding to localized regions of the monolayer lifted from the Petri dishes, which are good indicators of vectorialized ionic transport processes and differentiation state [9]. This concentration of DHT was also reported to be the most effective for maximal androgendependent transactivation of the pCAT1430 promoter in human breast-cancer cells [22], which was also used as a control in the present study.…”
Section: Androgen-dependent Transactivation Of the Kap Promoter In Momentioning
confidence: 91%
“…Several studies have shown that these two proximal-tubule cell lines have conserved the main features of the parental cells from which they were derived [6][7][8]. We also showed that levels of the kidney androgen-regulated protein (KAP) and β-glucuronidase ( β-gluc) transcripts, differentially expressed in two cultured PKSV-PCT and PKSV-PR cell lines, decreased when cells were shifted from a serum-supplemented to a steroid-free medium, whereas DHT induced a slight increase in β-gluc and a more marked increase in KAP transcripts in both cell lines [9].…”
Section: Introductionmentioning
confidence: 99%
“…After androgen stimulation, all three genes are expressed in epithelial cells of proximal convoluted tubules (segments S1 and S2) of cortical nephrons, but Kap is also expressed in the epithelial cells of proximal convoluted tubules in the juxtamedullary region (S3 segments). The differential effects of androgen action on ␤ -glucuronidase and Kap expression have been confirmed in immortalized proximal tubule cells (Ouar et al 1998).…”
Section: Discussionmentioning
confidence: 82%
“…Morphometric measurements indicated that the decreased expression of Kap in 1-month-old APRT-deficient male mice compared with wild-type controls was not the result of proximal tubule loss but may reflect the effects of hormonal changes in APRT deficiency. Androgens have a stimulating effect on cell growth through hypertrophy or hyperplasia (Preisig 1999), but in mouse kidney the primary effect appears to be hypertrophy (Ouar et al 1998). The growth stimulation seen in proximal tubules from APRT-deficient mice is due to hypertrophy rather than hyperplasia, and this effect may again be due to hormonal changes.…”
Section: Discussionmentioning
confidence: 99%